2018
DOI: 10.1007/s00330-018-5628-3
|View full text |Cite
|
Sign up to set email alerts
|

Motion-corrected multiparametric renal arterial spin labelling at 3 T: reproducibility and effect of vasodilator challenge

Abstract: Objectives We investigated the feasibility and reproducibility of free-breathing motion-corrected multiple inversion time (multi-TI) pulsed renal arterial spin labelling (PASL), with general kinetic model parametric mapping, to simultaneously quantify renal perfusion (RBF), bolus arrival time (BAT) and tissue T 1 . Methods In a study approved by the Health Research Authority, 12 healthy volunteers (mean age, 27.6 ± 18.5 years; 5 male) gave informed consent for renal imaging at 3 T using multi-TI ASL and conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Issues such as repeatability and validation of ASL with alternative methods to measure renal perfusion were extensively addressed therewith and, therefore, will not be covered in the present manuscript. The previous literature review [8] as well as 12 studies published in the intervening period [11][12][13][14][15][16][17][18][19][20][21][22], the results of a series of surveys and the discussions that took place at the in-person meetings form the basis for the final recommendations presented here.…”
Section: Previous Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Issues such as repeatability and validation of ASL with alternative methods to measure renal perfusion were extensively addressed therewith and, therefore, will not be covered in the present manuscript. The previous literature review [8] as well as 12 studies published in the intervening period [11][12][13][14][15][16][17][18][19][20][21][22], the results of a series of surveys and the discussions that took place at the in-person meetings form the basis for the final recommendations presented here.…”
Section: Previous Literature Reviewmentioning
confidence: 99%
“…Standardizing patient preparation with the aim of achieving more reproducible renal perfusion measurements may be desirable. Renal ASL perfusion estimates have shown significant variation when subjects were challenged with water loading, protein load, adenosine, and furosemide [20,[38][39][40].…”
Section: Patient Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Shirvani et al, showed recently the feasibility of multiparametric renal arterial spin labeling (3 T, 3D GRASE, FAIR, background suppression, and PD image acquired as the reference) with free-breathing acquisition [94]. The control and labeled images were motion-corrected by performing retrospective 2D elastic registration.…”
Section: Arterial Spin Labelingmentioning
confidence: 99%
“…3D GRASE has been increasingly used for perfusion imaging, both in the brain and kidneys . However, because of the linear or low‐high view ordering that is currently used, 3D GRASE images also suffer from signal variations and are often acquired using multiple signal averages .…”
Section: Discussionmentioning
confidence: 99%